Minutes of General Council (extract)
016a-0065-001 G.C. Minute 24 FEB. 1937 Item 47. Spain. In connection with this item, the Secretary read a report of the Joint meeting of the International Federation of Trade Unions and the Labour and Socialist Bureau, held on 17th February, 1937, which had been circulated attached to the Minutes of the International Committee. He added that Mr. Schevenels had prepared a report on his visit to Spain when he took a convoy of foods from the International Solidarity Fund. Members of the General Council would be supplied with this report for their personal information only. A brief discussion then took place on the Demonstration in aid of the International Solidarity Fund, to be held on Wednesday, 10th March, 1937, during the International Conference to be held in London. On the motion of Mr. Hallsworth, the Secretary's Report was ADOPTED. It was understood that the General Council members would attend the International Conference on the position in Spain, to be held in London on Wednesday, 10th March and Thursday, 11th March at 10 a.m., in accordance with the decision of the National Council of Labour, and that the proposed Demonstration would be held and that the Secretary make the necessary arrangements for the Agenda. 292/946/16a/66